2021
DOI: 10.1016/j.pedn.2021.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-emotional adjustment in parents of adolescents: A cross-sectional and longitudinal analysis of the impact of the COVID pandemic

Abstract: Purpose: adolescence is a time of change and it generally entails a greater family vulnerability thus; the aim of this study was to identify the risk factors for poor emotional adjustment to COVID among parents of adolescents. Design and methods: 94 parents of adolescents (11-18 years old, M = 13.90, SD = 1.85) participated at different times during the state of alert in Spain. 91.5% were mothers. Their ages ranged from 35 to 63 years (M = 46.54; SD = 5.09). The variables assessed were anxiety, depression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 39 publications
2
34
0
3
Order By: Relevance
“…To prevent its spread, the Governments of many countries worldwide, including Italy, planned a series of containment measures (e.g., physical distancing, school closures, and work from home), which severely affected the habits of individuals’ everyday lives, especially families with pre-school- and school-aged children [ 1 , 2 , 3 ]. Indeed, in addition to the resulting limitations of freedom, and health and economic concerns, parents of children aged from early childhood to middle adolescence [ 4 , 5 , 6 ] had to face a dramatic increase in the management of daily family life, their children’s care, and associated stress levels [ 7 ]. Due to the home confinement, the closure of educational services, and the lack of children’s interactions with teachers and peers, parents found themselves alone in the promotion of new learning experiences for their children [ 3 ], and in the management of home-schooling and social activities for school-aged children [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent its spread, the Governments of many countries worldwide, including Italy, planned a series of containment measures (e.g., physical distancing, school closures, and work from home), which severely affected the habits of individuals’ everyday lives, especially families with pre-school- and school-aged children [ 1 , 2 , 3 ]. Indeed, in addition to the resulting limitations of freedom, and health and economic concerns, parents of children aged from early childhood to middle adolescence [ 4 , 5 , 6 ] had to face a dramatic increase in the management of daily family life, their children’s care, and associated stress levels [ 7 ]. Due to the home confinement, the closure of educational services, and the lack of children’s interactions with teachers and peers, parents found themselves alone in the promotion of new learning experiences for their children [ 3 ], and in the management of home-schooling and social activities for school-aged children [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the home confinement, the closure of educational services, and the lack of children’s interactions with teachers and peers, parents found themselves alone in the promotion of new learning experiences for their children [ 3 ], and in the management of home-schooling and social activities for school-aged children [ 4 ]. Moreover, parents with early and middle adolescents (approximately from 11 to 16 years) [ 8 ] have had to face a substantial increase of conflicts with their children and, consequently, of their stress levels [ 6 , 9 ]. This could be due to the increment in the amount of time spent together during a stage of life in which, physiologically, adolescents tend to become more independent from parents, preferring to socialize with peers [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes at work, financial strain, and/or novel parenting responsibilities (e.g., homeschooling) during the COVID-19 pandemic may place additional demands on adult caregivers. Indeed, a longitudinal self-report study of parents of adolescents at the beginning of confinement in Spain demonstrated that those who had lost their job, had prior psychological problems, or lost someone to the pandemic showed worse emotional adjustment (Valero-Moreno et al, 2021). These increased demands threaten to overwhelm caregivers' internal resources (e.g., beliefs, cognitions) and may impede caregivers' abilities to engage in consistent parenting strategies (e.g., planning, monitoring, limit-setting).…”
mentioning
confidence: 99%
“…For example, in a research, it was determined that the emotional impact of the pandemic negatively affected the mental health and psychological resilience of parents and children. In addition, it was emphasized that families who had health problems before or who lost their job or a relative in the pandemic are more affected (Valero-Moreno et al, 2021). In another study, it was stated that the pandemic process, which negatively affected the physical and psychological health of families, negatively affected happiness (Ohlbrecht & Jellen, 2021).…”
Section: Resultsmentioning
confidence: 99%